«ECOLOGICAL BOOMERANG» EFFECT IN HOSPITAL ENVIRONMENT - Besarion C. Meskhi; Vyacheslav A. Zimenko; Olga V. Dymnikova (Advanced Engineering Research, 2012)
Some dangerous, in terms of the man-made ecosystem operation, events in the hospital environment are presented. The microbiological factor, its transformation in the course of the diagnostic and treatment process, and human health implications are considered.